2018
DOI: 10.1590/0102-7786334005
|View full text |Cite
|
Sign up to set email alerts
|

Climatologia de Chuvas Intensas no Município do Rio de Janeiro

Abstract: ResumoNeste trabalho elabora-se uma climatologia de eventos de chuvas intensas (ECIs) no Município do Rio de Janeiro (MRJ) a partir dos dados observados pelo Sistema Alerta Rio no período 1997-2016. Um critério objetivo de identificação de ECIs é avaliado, confrontando-se dados de chuva com informações sobre os transtornos deflagrados por tais eventos sobre a cidade. O critério estabelece que um ECI se caracteriza por um total pluviométrico diário igual ou superior a seu percentil 95, com ocorrência no mesmo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Besides that, specifically in the Rio de Janeiro state during the austral summer, higher rainfall rates are also chiefly driven by the presence of SACZ and FS systems (Fig. 4 right), in general, related to single-cell or multicellular thunderstorms (Silva et al 2019;Pristo et al 2018;Lima et al 2021). precipitation distribution are noted with the increased grid resolution.…”
Section: Summer Storm Events and Meteorological Systems Associatedmentioning
confidence: 94%
“…Besides that, specifically in the Rio de Janeiro state during the austral summer, higher rainfall rates are also chiefly driven by the presence of SACZ and FS systems (Fig. 4 right), in general, related to single-cell or multicellular thunderstorms (Silva et al 2019;Pristo et al 2018;Lima et al 2021). precipitation distribution are noted with the increased grid resolution.…”
Section: Summer Storm Events and Meteorological Systems Associatedmentioning
confidence: 94%
“…The presence of three massifs (Tijuca, Pedra Branca and Gericinó), the proximity of the Atlantic Ocean, the Guanabara Bay and the Sepetiba Bay (Fig. 1), produce a great spatial variability of precipitation in the region, which according to Pristo et al (2018) varies between 912 mm of total annual rainfall in the north of the city and 2546 mm over the Tijuca massif.…”
Section: Introductionmentioning
confidence: 99%
“…For the state of Rio de Janeiro and its capital, changes in rainfall distribution were also identified, along with increase in extreme events related to precipitation, and impacts on population were quantified by Aguiar and Cataldi (2021); Avila et al (2016); Bunhak and Wanderley (2020); Ehrlich et al (2021); Machado et al (2010); Pereira et al (2021). Pristo et al (2018); Silva and Dereczynski (2014); Silva et al (2016) and Wanderley and Bunhak (2016) showed the importance of studying precipitation, its changes and impacts.…”
Section: Introductionmentioning
confidence: 99%